A Systematic Review of Passion and Personality Traits as Catalysts for Well-Being and a Growth Mindset - Aalap Patel; Veena Patel (Greenation Research & Yayasan Global Resarch National, 2025)
This systematic review synthesizes literature on how passion and personality traits function as psychological antecedents for well-being and the development of a growth mindset. Drawing upon 60 peer-reviewed articles from 2013 to 2025, this paper investigates the dynamic interactions between harmonious/obsessive passion, Big Five personality traits, and constructs such as grit, self-efficacy, emotional resilience, and mindset adaptability. Following the PRISMA 2020 guidelines, eligible studies were identified through structured queries across multiple databases including Scopus, Web of Science, Taylor & Francis, and PubMed. A bibliometric content analysis was conducted using keyword co-occurrence and author collaboration mapping. Key findings indicate that passion acts as a motivational engine, while personality traits provide cognitive scaffolding for well-being and mindset development. Harmonious passion is consistently linked with emotional regulation, grit, and flourishing, while conscientiousness and openness predict adaptive behaviors and mindset shifts. The review highlights research gaps related to longitudinal integration, cross-cultural variability, and underexplored moderating factors like digital immersion and resilience scaffolding. Implications for educational settings, organizational behavior, and entrepreneurial leadership are discussed, with recommendations for interdisciplinary and intervention-focused future research.